2016
DOI: 10.1589/jpts.28.72
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the stomatognathic system on explosive strength: a pilot study

Abstract: [Purpose] Recent findings suggest there is an interesting interaction between the stomatognathic system and the musculoskeletal system. The aim of this study was therefore to examine the influence of the temporomandibular joint on the explosive strength of the lower limbs. [Subjects and Methods] An observational study was carried out. The subjects were 60 male football players who voluntarily participated in the investigation. After a warm-up phase of 10 minutes, each participant performed three Squat Jumps (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
9
0
6
Order By: Relevance
“…The central nervous system interprets, integrates and selects information from various sensory inputs (somatosensory, visual and vestibular) to produce required motor outputs to maintain static and dynamic balance 1 ) . Sport-specific training can influence the postural system through its influence on sensory organization and the reinforcement of specific balance strategies 2 , 3 , 4 ) . As an example, Del Percio et al reported that karate-trained athletes had a better ability to analyse and integrate sensory inputs for balance control than a control group 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The central nervous system interprets, integrates and selects information from various sensory inputs (somatosensory, visual and vestibular) to produce required motor outputs to maintain static and dynamic balance 1 ) . Sport-specific training can influence the postural system through its influence on sensory organization and the reinforcement of specific balance strategies 2 , 3 , 4 ) . As an example, Del Percio et al reported that karate-trained athletes had a better ability to analyse and integrate sensory inputs for balance control than a control group 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The static baropodometry analyses was managed with the FreeMed software (the FreeStep v.1.0.3 software, produced by Sensor Medica, Guidonia Montecelio, Roma, Italy). The platform's sensors are 24K gold; this allows high repeatability and reliability [26]. Using the Romberg test position, all subjects were administered podalic analysis on the baropodometric platform.…”
Section: Methodsmentioning
confidence: 99%
“…16 Bununla birlikte, yapılan pilot bir çalışmada mandibulanın kasiskelet sistemi üzerinde patlayıcı kuvveti etkilediği ve değişime sebep olduğu gösterilmiştir. 7 Bu değişimin ana aktörünün ise afferent ve efferent sinir yollarına sahip olan beşinci kafa çifti N. trigeminus olduğu düşülnülmektedir. [17][18][19] Postüral kontrole karışan sinirsel yapılar ile trigeminal sistem arasında tarif edilen sayısız anatomik ilişki mevcuttur.…”
Section: Bulgularunclassified
“…20 Çalışmalarda, mandibular çene pozisyonunun fiziksel performansı etkilediği gösterilmiş olsa da üzerinde durulan diğer bir konu trigeminal sinir ve kas-fasiyal yapı zinciri arasındaki ilişkidir. 7 Fasiyal sistem mekanik olarak uyarıldığında, vücut kaslarındaki gerilimi pasif olarak dağıtabileceği gibi, mekanik reseptörler içerdiği ve fasiyal gerginliği etkileyen otonom kontraktil bir yeteneğine sahip olduğu için önemlidir. 21 Ayrıca, diş çekimine bağlı olarak gelişen lokal ve sistemik inflamatuar değişimler, çalışmamızda yüzde olarak ortaya çıkan kas performansındaki düşüşün nedeni olabileceğini düşünmekteyiz.…”
Section: Bulgularunclassified
See 1 more Smart Citation